How Kalanchoe marmorata (Crassulaceae subfam. Kalanchooideae), a distinctive central and east African species, received its name, and the later, valid publication of K. macrantha by Maire - Smith, Gideon F. (Phytotaxa, 2021)
Aspects of the nomenclature of Kalanchoe marmorata (Crassulaceae subfam. Kalanchooideae), which was validly published in 1892, are discussed and clarified. Although mentioned, but not validly published, by John G. Baker in 1892, K. macrantha was eventually validly published in 1976 in the volume of the Flore de l’Afrique du Nord that included the Crassulaceae, a posthumous treatment of the family by René C.J.E. Maire. However, K. macrantha, although a validly published name, is illegitimate as the earlier published K. marmorata was included in the synonymy of one of its varieties. The nomenclature of the three varieties that Maire recognised in K. macrantha is discussed. The typification of the names K. grandiflora and K. marmorata is clarified.